(untitled) (Asian Journal of Social Science Studies, 2026)
Go-Jek online transportation contributes to the national economy through partnerships with MSMEs. This study focuses on the perceptions of Micro, Small and Medium Enterprises (MSME) entrepreneurs in the culinary field of Go-Jek online transportation in Pontianak City. The purpose of this study was to find out the perceptions and constraints of MSME entrepreneurs in the culinary field in the city of Pontianak after collaborating with online transportation Go-Jek. The study uses descriptive methods with a qualitative approach. The findings of this study are the perceptions of small and medium micro entrepreneurs (MSMEs) in the culinary field in the city of Pontianak on Go-Jek online transportation which is very positive, useful and helps MSME entrepreneurs. Whether it’s in product promotion, or in delivering products to consumers. The impact that is also directly felt by MSME entrepreneurs on online transportation is that business revenues increase by 10% to 30%. The obstacles faced are first, the existence of fraud committed by the individual drivers of Go-Jek online transportation to MSMEs and consumers, by buying products ordered by consumers, but not in the shop in question. Both driver services to MSMEs are not polite and unfriendly.